Management of Gastric Varices Unsuccessfully Treated by Balloon-Occluded Retrograde Transvenous Obliteration: Long-Term Follow-Up and Outcomes - Fumio Uchiyama; Satoru Murata; Shiro Onozawa; Ken Nakazawa; Fumie Sugihara; Daisuke Yasui; Yoshiyuki Narahara; Eiji Uchida; Yasuo Amano; Shin-ichiro Kumita (The Scientific World Journal)
Our aim was to evaluate the long-term efficacy and safety of percutaneous transhepatic obliteration (PTO) alone and combined with balloon-occluded retrograde transvenous obliteration (BRTO) for gastroesophageal varices refractory to BRTO alone. Between July 1999 and December 2010, 13 patients with gastroesophageal varices refractory to BRTO were treated with PTO (n = 6) or a combination of PTO and BRTO (n = 7). We retrospectively investigated the rates of survival, recurrence, or worsening of the varices; hepatic function before and after the procedure; and complications. The procedure achieved complete obliteration or significant reduction of the varices in all 13 patients without major complications. During follow-up, the varices had recurred in 2 patients, of which one had hepatocellular carcinoma, and the other died suddenly from variceal rebleeding 7 years after PTO. The remaining 11 patients did not experience worsening of the varices and showed significant improvements in the serum ammonia levels and prothrombin time. The mean follow-up period was 90 months, and the cumulative survival rate at 1, 3, and 5 years was 92.9%, 85.7%, and 85.7%, respectively. Both PTO and combined PTO and BRTO seem as safe and effective procedures for the treatment of gastroesophageal varices refractory to BRTO alone.